Pattern of External Insertion, Foreign Capital and Ecologically Unequal Exchange in the Post-Neoliberal South America - Belloni, Paula; Peinado, Guillermo (Sociedad y Economía, 2013)
In recent years the South American region has increased its historic external insertion basedon the extraction of natural resources. This revives the discussion on patterns of dependentdevelopment in a new phase of the global economy. In this context, the purpose of this workis to characterize the external insertion pattern of the region during the post-neoliberal period,with special emphasis on the effects of foreign capital over external sector dynamics,the ecological terms of exchanges and their potential impacts on natural capital. Finally, itreflects on the old and new roles that the international integration of South America hasin the current dynamic of global accumulation.